Maintaining Social Interaction in the Covid-19 Pandemic Era - Mahmudi Mahmudi (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Coronavirus Desease 2019 (Covid-19) is a disease outbreak that emerged in Wuhan, China in December 2019. The emergence of Coronavirus Desease 2019 (Covid-19) caused a stir in people's lives in most parts of the world. Covid-19 is a virus that spreads quickly and easily. Crowds are one of the media for the spread of this virus, so crowds must be eliminated in order to stop its spread. Stopping the crowd has the potential to destroy the social fabric in society. Thus, good social interaction is susceptible to deterioration due to the presence of this virus. That is what attracts the author in conducting research with the title